BIOPROCESS APPLIED TO THE TREATMENT OF RESIDUAL WATERS OF COFFEE WET PROCESSING FOR THE INCORPORATION OF SELECTED YEAST STRAINS - BEUX, MARCIA REGINA; YAMAMOTO, CARLOS ITSUO; WINTER, CRISTINA MARA GUOLO; RAMOS, WILTON FONTES; BARBIERI, FABIANA NICOL; FERREIRA, JOSÉ LAURENTINO; SOCCOL, CARLOS RICARDO (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2003)
O objetivo deste trabalho foi isolar cepas de leveduras capazes de degradar a água de degomagem do beneficiamento úmido do café, caracterizando os metabólitos formados. A bebida preparada a partir de grãos tratados por via úmida é considerada de melhor qualidade quando comparada à elaborada com grãos tratados por via seca. No entanto, o alto potencial poluente da água residual do beneficiamento representa sério problema para o ambiente. A água de degomagem apresenta essencialmente contaminação orgânica, com taxas de demanda bioquímica de oxigênio (DBO) e demanda química de oxigênio (DQO) superiores a 20.000 mgO2/L. Candida tropicalis, C. lypolitica, C. guilliermondii, C. parapsilopsis, Kloeckera apiculata e Rhodotorula rubra, isoladas de cerejas de café, foram inoculadas em frascos contendo água de degomagem e esses, submetidos à agitação constante(120 rpm) por 48 horas, a 28oC. Candida parapsilopsis apresentou percentual de redução da taxa de DBO de 50,14% e de DQO de 29,81%, evidenciando a viabilidade do uso desses microrganismos como biodespoluentes. DESENVOLVIMENTO DE BIOPROCESSO APLICADO AO TRATAMENTO DE ÁGUAS RESIDUAIS DO BENEFICIAMENTO ÚMIDO DO CAFÉ PELA INCORPORAÇÃO DE LINHAGEM SELECIONADA DE LEVEDURAS Abstract The aim of the present work was to isolate yeast strains able to degrade the degumming water originated from the wet processing of coffee, characterizing the formed metabolites. The drink prepared from the treated grains by wet processing is considered of better quality when compared with the grains treated by dry process. However, the great polluent potential of the residual water from this processing represents serious concern for the environment. The degumming water essentially presents organic contamination, with Oxygen Biochemical Demand (OBD) and Oxygen Chemical Demand (OCD) rates superior to 20.000 mgO2/L. Candida tropicalis, C. lypolitica, C. guilliermondii, C. parapsilopsis, Kloeckera apiculata e Rhodotorula rubra, isolated from coffee cheeries were inoculated in flasks containing the degumming water and then submitted to constant agitation (120 rpm) for 48 hours at 28ºC. The isolated species revealed capacity to degrade the substrate, however C.parapsilopsis showed reduction percentages of OBD and OCD rates of 50.14% e 29.81%, respectivelly, showing the viability of the use of those microorganisms as biological depollutants.